Literature Review : The Effect Of Ginger (Zingiber Officinale Var. Amarum) And Honey On Blood Pressure Reduction - Fifi Luthfiyah; Mita Anggraeni; Retno Wahyuningsih (Fakultas Ilmu Kesehatan Universitas Gresik, 2022)
The prevalence of hypertension in NTB at 2018 was 27.8%, this figure was higher than 2013, which was 24.3%. Hypertension management can be done pharmacologically and non pharmacologically. Non pharmacological therapy can be done by consuming honey and ginger. Honey and ginger contain chemical components that can help lower blood pressure. To conduct a literature study on the effect of ginger (Zingiber officinale var. Amarum) and honey on reducing blood pressure. The literature search in this literature review was carried out using five databases with low to high quality, namely Scopus, ProQuest, Pubmed, Garuda Garba, and Google Schoolar. The keywords used are